시·군 기초생활권 정책 발전방안 구상 - 송미령 (한국농촌경제연구원, 2008)
The aim of this study is to establish a policy direction so that a schema for the development of ‘Basic Settlement Areas’ can be drawn up in earnest. The proposed ‘Basic Settlement Areas’ program is one of the underpinning elements in three dimensional framework of regional development policies of the current government of President Lee, namely four major axes of East Coastal Axis, South Coastal Axis, West Coastal Axis and East-West Inland Axis, "5+2" Area-Wide Economic Zones, and 162 Basic Settlement Areas. Unlike the other two, 162 Basic Settlement Areas are delineated explicitly to satisfy immediate needs of residents for basic services. First, the theoretical meaning of ‘Basic Settlement Area’ is carefully studied as an extension of the previous conception of ‘Human Settlement Areas’, and then, basic conditions and characteristics are analyzed, compared and classified into different types. Secondly, a number of policy directions for the ‘Basic Settlement Area’ program to be effective in raising quality-of-life and welfare of each resident are suggested. Finally, contents of the program and measure to improve program outputs at each stage of the program are put forward. 162 Basic Settlement Areas, in various types of ‘urban’, ‘rural’, and ‘urban-rural linked’, do differ from previous Human Settlement Areas in their actual conditions and characteristics. Considering the program’s mandate, that is, to satisfy immediate needs of residents for basic services, and local governments’ familiarity with local conditions, local governments, rather than the central government, must push forward with the program. Especially to warrant effective program outcomes, policy guidelines must be established for various groups of policies respectively in advance so that planning and policy implementation can follow the guidelines. In addition, a system of incentives and penalties, in conjunction with a measure for the evaluation of program outcomes, must be built into the program. Researchers: Mi-Ryung Song, Dong-Phil Lee, Ju-Young Park Research Period: 2008.7.～2008.10. E-mail Address: mrsong@krei.re.kr